MANAJEMEN PEMBELAJARAN ANAK USIA DINI MELALUI METODE BERCERITA DALAM PENGEMBANGAN KARAKTER DI TK NEGERI HINDU WIDYA KUMARA PAYANGAN GIANYAR: MANAJEMEN PEMBELAJARAN ANAK USIA DINI MELALUI METODE BERCERITA DALAM PENGEMBANGAN KARAKTER DI TK NEGERI HINDU WIDYA KUMARA PAYANGAN GIANYAR - Suyanta, I Wayan; Sedana Suci, I Gede (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2024)
It is very important for educational managers to pay attention to the material provided. The purpose of this study is to analyze and describe teaching methodologies using storytelling approach in character development of young Indonesian citizens. This qualitative descriptive research is being conducted in kindergarten. Hindu Widya Kumara State in Payangan District, Gianyar. Triangulation techniques are used in data collection methods such as surveys, observations, and documentation. To analyze data, use the Miles and Huberman model, which consists of data reduction, data augmentation, data size, and verification. Based on research findings, teaching methods for teaching early childhood are implemented through the use of storytelling, which includes observation, discussion, implementation, and evaluation.